IMPACT OF FINANCING DECISIONS ON FIRMS PERFORMANCE: AN EMPIRICAL STUDY OF PAKISTANI LISTED FIRMS IN KSE (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
The basic purpose of our research paper is to analyze the impact of financing decisions on the firms performance in Pakistani listed firms in KSE. The OLS has been employed on a sample of conveniently selected 100 pakistanilisted firms in KSE (with 600 observations) over the period of 2004 to 2009.Financing decisions are measured through debt to equity and firms performance measured through ROE, ROA, Tobins Q and market capitalization.Ourresults show that the financing decisions have no significant impact on firms performance in Pakistan.